Plasmonic resonance instigated enhanced photoluminescence in quantum dot dispersed nematic liquid crystal. Issue 8 (21st June 2019) - Roy, Aradhana; Agrahari, Kaushlendra; Srivastava, Atul; Manohar, Rajiv
ABSTRACT: In the present investigation, the optical property of the nematic sample p -methoxybenzylidene p -decylaniline, dispersed with SiO2 quantum dot (QD), has been reported. Enhanced luminescence has been observed from nematic-QD composites. Surface plasmonic effect along with QD exciton has been highlighted to discuss the observed intensification in photoluminescence. The intensified photoemission from the nematic composites can also be inferred from improved orientational behaviour of the liquid crystal molecules due to dispersion of QDs. Variation in the intensity of photoabsorption can be harnessed for development of luminescent display devices and optical parameter-driven scientific applications. Graphical Abstract: